2010
DOI: 10.1148/radiol.09090548
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pulmonary Hypertension with Multidetector CT and Echocardiography Alone and in Combination

Abstract: Purpose:To test the reliability of potentially new computed tomographic (CT) indicators of pulmonary hypertension (PH) and to establish whether a combination of CT and echocardiographic measurements was more predictive of PH than either test alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(137 citation statements)
references
References 26 publications
3
133
0
1
Order By: Relevance
“…However, most of these studies were conducted in heterogeneous populations with various underlying lung diseases, thus, limiting their application to patients with COPD. [14][15][16][17][18][19][20] We showed that CT image-measured relative PA enlargement, defined as a PA:A ratio . 1, identifies patients at increased risk of COPD exacerbation and hospitalization 21 ; however, the mechanism underlying relative PA enlargement has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies were conducted in heterogeneous populations with various underlying lung diseases, thus, limiting their application to patients with COPD. [14][15][16][17][18][19][20] We showed that CT image-measured relative PA enlargement, defined as a PA:A ratio . 1, identifies patients at increased risk of COPD exacerbation and hospitalization 21 ; however, the mechanism underlying relative PA enlargement has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although neither sign appears to be sufficiently accurate in isolation, the combination of HRCT and echocardiography was found in one study to perform better in PH detection than the use of either individual test [75].…”
Section: Diagnosismentioning
confidence: 94%
“…However, no linear correlation has been found between pulmonary artery diameter and the severity of PHT. Also, pulmonary artery dilatation can occur in the absence of PHT in patients with pulmonary fibrosis and is therefore an unreliable sign of PHT in this cohort [51]. Devaraj et al [52] showed that a composite index of the ratio of the diameter of the MPA and ascending aorta combined with echocardiography-derived right ventri- Right heart on multidetector CT…”
Section: Pulmonary Hypertensionmentioning
confidence: 80%